2017
DOI: 10.3389/fmicb.2017.00146
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Markers and Phylogenetic Analysis of Escherichia coli Strains with Hybrid EAEC/UPEC Genotypes Recovered from Sporadic Cases of Extraintestinal Infections

Abstract: Virulence genes from different E. coli pathotypes are blended in hybrid strains. E. coli strains with hybrid enteroaggregative/uropathogenic (EAEC/UPEC) genotypes have sporadically emerged causing outbreaks of extraintestinal infections, however their association with routine infections is yet underappreciated. We assessed 258 isolates of E. coli recovered from 86 consecutive cases of extraintestinal infections seeking EAEC and hybrid genotype (EAEC/UPEC) strains. Extensive virulence genotyping was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 40 publications
7
49
1
5
Order By: Relevance
“…Interestingly, Olesen et al [34] found that the EAEC isolates of serotype O78:H80 and ST10 were responsible for an outbreak of UTI in Denmark. On their side, Abe et al [35] and Lara et al [36] found some UPEC isolates with properties of EAEC in Brazil, including hybrid UPEC/EAEC ST69, ST73 and ST131 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Olesen et al [34] found that the EAEC isolates of serotype O78:H80 and ST10 were responsible for an outbreak of UTI in Denmark. On their side, Abe et al [35] and Lara et al [36] found some UPEC isolates with properties of EAEC in Brazil, including hybrid UPEC/EAEC ST69, ST73 and ST131 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence in UPEC 252 of genes characteristic of DEC, the isolation of an symptomatic urinary tract infection, and the presence of ExPEC traits simultaneously suggests that it may cause infections in both the intestinal and extraintestinal tracts, and can be classified as a hybrid aEPEC/UPEC strain (Santos et al, 2020a ). Likewise, Lara et al ( 2017 ) identified two UPEC strains carrying EAEC and UPEC genes simultaneously. In the same study, an E. coli strain isolated from bacteremia with the same hybrid characteristics as the UPEC strains was also found.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recognized potential of HGT between pathogenic E. coli strains, only a few studies have described this phenomenon among DEC and UPEC in strains isolated from UTI and in these studies the genetic background of strains involved was not evaluated (Olesen et al, 1994 ; Garcia et al, 2000 ; Keller et al, 2002 ; Matar et al, 2005 ; Ogura et al, 2007 ; Wallace-Gadsden et al, 2007 ; Abe et al, 2008 ; Lara et al, 2017 ; Santos et al, 2020a ). A study evaluating fecal EAEC isolates identified that some strains produced alpha-hemolysin ( hlyA ) and P fimbria ( pap ) (Suzart et al, 1999 ), characteristics often found in UPEC strains, suggesting that certain EAEC strains with specific virulence genes would be potentially uropathogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, four (9%) of the isolates did not reveal any ExPEC or UPEC associated VF and in addition remained susceptible to all antimicrobials tested. Since UTI is sporadically caused by EAEC (Herzog et al, 2014 ; Lara et al, 2017 ), these four isolates were screened for the EAEC marker gene aggR . However, all remained negative and the virulence mechanisms of these UPEC isolates remain to be further characterized.…”
Section: Discussionmentioning
confidence: 99%